2013
DOI: 10.1038/hdy.2013.72
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of segregation and recombination on the evolution of sex in finite diploid populations

Abstract: The mechanism of reproducing more viable offspring in response to selection is a major factor influencing the advantages of sex. In diploids, sexual reproduction combines genotype by recombination and segregation. Theoretical studies of sexual reproduction have investigated the advantage of recombination in haploids. However, the potential advantage of segregation in diploids is less studied. This study aimed to quantify the relative contribution of recombination and segregation to the evolution of sex in fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…'sex without recombination' versus 'no sex') and those favoring recombination per se (i.e. 'sex with recombination' versus 'sex with no recombination') are not the same [35,36]. In general, empirical studies do support the RQH, although the evidence remains very limited for sex [37][38][39][40][41][42] and even more so for recombination [43,44].…”
mentioning
confidence: 95%
“…'sex without recombination' versus 'no sex') and those favoring recombination per se (i.e. 'sex with recombination' versus 'sex with no recombination') are not the same [35,36]. In general, empirical studies do support the RQH, although the evidence remains very limited for sex [37][38][39][40][41][42] and even more so for recombination [43,44].…”
mentioning
confidence: 95%
“…Each parameter combination was run 10 times and the standard error was calculated. We did not consider different selection coefficients, because various selective strength had been studied previously by our group [ 18 ]. This research concentrated on the influence of dominance with constant selective coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Agrawal (2009) compared their relative effects by using mutation–selection balance model with three loci [ 17 ] and demonstrated that as an important factor, migration between genetically differentiated populations could impact the evolution of sex by influencing segregation. In a previous study, we also showed that in multi–locus models, the combined effects of segregation and recombination strongly contributed to the evolution of sex in diploids [ 18 ]. However, another critical determinant, the dominance coefficient, h , was not considered in that study.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical models that underpin the Deterministic Mutation Hypothesis further show that the evolution of sex can be favored even in the absence of small population sizes, under conditions in which the majority of mutations are slightly deleterious, their effects positively epistatic, and the mutation rate high . Other models indicate that population demographics and the specific properties of mutations will affect the dynamics of mutation accumulation within asexual populations, and thus alter the conditions under which the evolution of sex will be favored . Empirical studies have generally substantiated these mutation‐based theories of sex (see as an example of an exception).…”
Section: Previous Links Between Mutations Mitochondria and The Evolmentioning
confidence: 99%